2022
DOI: 10.3390/polym14153170
|View full text |Cite
|
Sign up to set email alerts
|

Thiolated 2-Methyl-β-Cyclodextrin as a Mucoadhesive Excipient for Poorly Soluble Drugs: Synthesis and Characterization

Abstract: Thiolated cyclodextrins are structurally simple mucoadhesive macromolecules, which are able to host drugs and increase their apparent water solubility, as well as interact with the mucus layer prolonging drug residence time on the site of absorption. The aim of this study was to synthesize through green microwave-assisted process a freely soluble thiolated 2-methyl-β-cyclodextrin (MβCD-SH). Its inclusion complex properties with dexamethasone (Dex), a poor water soluble drug, and mucoadhesive characteristics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The DLS analysis of the BEO/QA-Ch-MCD conjugate showed that the conjugation process led to agglomerates with nanometer size, not different from those formed from BEO/MCD. However, the agglomerates obtained from BEO/QA-Ch-MCD had a more inhomogeneous distribution than those from BEO/MCD, as demonstrated by the PdI values, which confirms the ability of CD host/guest complexes to self-assemble in water [ 23 , 24 ]. In both cases, the ζ-potential absolute values indicate that the agglomerates were reasonably stable, leading to a colloidal dispersion of the lipophilic compounds [ 25 ].…”
Section: Resultsmentioning
confidence: 87%
“…The DLS analysis of the BEO/QA-Ch-MCD conjugate showed that the conjugation process led to agglomerates with nanometer size, not different from those formed from BEO/MCD. However, the agglomerates obtained from BEO/QA-Ch-MCD had a more inhomogeneous distribution than those from BEO/MCD, as demonstrated by the PdI values, which confirms the ability of CD host/guest complexes to self-assemble in water [ 23 , 24 ]. In both cases, the ζ-potential absolute values indicate that the agglomerates were reasonably stable, leading to a colloidal dispersion of the lipophilic compounds [ 25 ].…”
Section: Resultsmentioning
confidence: 87%
“…The diffusion of coumarin-6, complexed in native β-CD, β-CD-SH, and β-CD-SS-MESNA into purified porcine intestinal mucus, was studied via the rotating tube method, as described previously. , In brief, silicone tubes were cut into 50 mm long pieces and filled with 250 μL of purified porcine intestinal mucus. Afterward, 50 μL of 1% (m/v) complexes in 50 mM phosphate buffer pH 6.8 was added to the mucus-filled tubes.…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of the polymer diffused into the mucus was calculated based on a calibration curve. 12,15 Statistical Data Analysis. Statistical analyses of all data were implemented using Student's t-test, with a confidence interval (CI) of p < 0.05.…”
Section: Rmfi Mfi /Mfi 1 Sample Controlmentioning
confidence: 99%
See 2 more Smart Citations